Penggunaan Fiber Tissue Sebagai Media Penyerap Elektrolit pada Dye Sensitized Solar Cell - Wisaksono, Muaffan Alfaiz; Tamrin, Tamrin; Pratama, Filli (Seminar Nasional Lahan Suboptimal, 2024)
Wisaksono, M. A., Tamrin, T., Pratama, F. (2024). The utilization of fiber tissue as an electrolyte absorbent of Dye Sensitized Solar Cell. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 634–648). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Dye-Sensitized Solar Cells represent a set of photoelectrochemical solar cells capable of converting light energy into electrical energy by harnessing plant-derived dyes as light sensitizer. One of the factors influencing the performance of a DSSC is the electrolyte. The addition of a fiber tissue layer to DSSCs can reduce evaporation in the electrolyte solution. The fiber tissue layers used in this study were derived from facial tissue. The objective of this research is to study and understand the impact of varying thicknesses of fiber tissue layers as electrolyte absorption media on the performance of Dye-Sensitized Solar Cells. This research was conducted from September 2023 to December 2023 at the Energy and Electrification Laboratory, Department of Agricultural Technology, Faculty of Agriculture, Universitas Sriwijaya. The study comprised of three stages: DSSC structure preparation, assembly and arrangement of DSSC layers, and DSSC measurements. The thickness variations of the fiber tissue layers used were two layers (0,027 cm), three layers (0,041 cm), four layers (0,054 cm), five layers (0,068 cm), six layers (0,081 cm), and a control without fiber tissue layer applied to water hyacinth leaf dye and senduduk fruit dye. Parameters observed in this study included current and voltage characteristics, power calculations, fill factor, and DSSC efficiency. The results indicated that DSSCs with an additional fiber tissue layer exhibited relatively better performance compared to DSSCs without the additional fiber tissue layer, both in the senduduk fruit dye and water hyacinth dye.. The DSSC performance was most prominent in the senduduk fruit dye sample with a four-layer (0.054 cm) thickness of fiber tissue layer. The electrical characteristics produced by this sample were Isc:  0,016 mA, Voc:  0,682 mV, Imax:  0,011 mA, Vmax:  0,397 mV, Pmax:  0,00417 mW, FF:  0,37924, and an efficiency of 0,016%.